2007
DOI: 10.1111/j.1467-8683.2007.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management and Corporate Governance in Asia's Emerging Markets

Abstract: This paper studies the impacts of corporate governance on earnings management. We use firm-level governance data, taken from Credit Lyonnais Security Asia (CLSA), of nine Asian countries, in addition to the country-level governance data used in past studies. Our conclusion is as follows. First, firms with good corporate governance tend to conduct less earnings management. Second, there is a size effect for earnings smoothing, that is, large size firms are prone to conduct earnings smoothing, but good corporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 29 publications
2
85
0
1
Order By: Relevance
“…For example, Klein (2002) found that firms with boards and/or audit committees composed of independent directors are less likely to have larger abnormal accruals. In the same manner, Shen and Chih (2007) found that effective corporate governance mechanism tend to conduct less earnings management. Additionally, Abdul Rahman and Ali (2006) and Epps and Ismail (2008) confirmed that board characteristics are important determinants of earnings management.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 74%
“…For example, Klein (2002) found that firms with boards and/or audit committees composed of independent directors are less likely to have larger abnormal accruals. In the same manner, Shen and Chih (2007) found that effective corporate governance mechanism tend to conduct less earnings management. Additionally, Abdul Rahman and Ali (2006) and Epps and Ismail (2008) confirmed that board characteristics are important determinants of earnings management.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 74%
“…Literature on disclosure quality and earnings management proxies for disclosure quality ranges to AIMR ratings (Zhou and Lobo 2001), disclosure index and compliance to accounting standards (Lapointe-Antunes et al 2006;Shen and Chih 2007), voluntary disclosure (Iatridis and Kadorinis 2009) and press releases by the firms (Jo and Kim 2007;Riahi and Arab 2011) etc. These studies in the US, Switzerland, Tunisia and the UK capital market have consistently documented a negative relationship between disclosure quality and earnings management.…”
Section: Literature Review and Hypotheses Development Literature Reviewmentioning
confidence: 99%
“…Prior studies argue that earnings management is dependent on the extent of a firm's disclosure transparency (Jo and Kim 2007) and corporate governance (Shen and Chih 2007). Disclosure and corporate governance are monitoring tools that operate within a firm's governance system, and which are potentially useful for reducing information asymmetry and reducing agency cost (Hope and Thomas 2008;Holm and Schøler 2010;Arcot and Bruno 2011).…”
Section: Literature Review and Hypotheses Development Literature Reviewmentioning
confidence: 99%
“…The CLSA score rates firms on their management discipline, transparency, independence, accountability, responsibility, fairness and social awareness. Shen and Chih (2007) use CG data from the CLSA for 9 Asian countries (Hong Kong, India, Indonesia, Korea, Malaysia, Philippines, Singapore, Taiwan and Thailand) and find firms with better CG have less earnings management and less earnings smoothing. Other evidence of earnings smoothing is provided in a study of Taiwanese firms' use of reversal of impairment losses between 2005 and 2007 after the introduction of IAS 36, Impairment of Assets.…”
Section: Earnings Managementmentioning
confidence: 99%